2021
DOI: 10.3390/polym13183189
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Mechanism of Nanofiber Yarn and Its Multiscale Wrapping Yarn

Abstract: To analyze the feasibility of electrospinning nanofiber yarn using a wrapping yarn forming device, electrospun nanofiber-wrapped yarns and multiscale yarns were prepared by self-made equipment. The relationship between the surface morphology and properties of yarn and its preparation process was studied. The process parameters were adjusted, and it was found that some nanofibers formed Z-twisted yarns, while others showed exposed cores. To analyze the forming mechanism of electrospun nanofiber-wrapped yarn, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…f) Reproduced with permission. [ 5 ] Copyright 2021 by the authors. Licensee MDPI, Basel, Switzerland.…”
Section: Electrospinningmentioning
confidence: 99%
See 3 more Smart Citations
“…f) Reproduced with permission. [ 5 ] Copyright 2021 by the authors. Licensee MDPI, Basel, Switzerland.…”
Section: Electrospinningmentioning
confidence: 99%
“…Instead of nonwoven fabric collected on a flat pate, nanofiber yarn is fabricated by a rotating funnel [ 5 ] (Figure 4f). It was reported that the nanofiber yarn can have high strength in combination with high toughness.…”
Section: Electrospinningmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of composite DC spinning yarns has been successfully tested via a number of previous experimental studies . Nevertheless, the main drawback of the DC technique concerns the requirement for a charged/grounded counter electrode. , Thus, AC spinning, which does not require a counter electrode, appears more suitable for the fabrication of composite yarns.…”
Section: Introductionmentioning
confidence: 99%